A picture is worth a thousand words: A proposal to incorporate video into the evaluation of adults with intellectual or developmental disability living outside the home - Prager, Briana C.; Broder, Sherri M.; Natowicz, Marvin R. (Frontiers in Public Health, 2022)
Adults with intellectual or developmental disability (IDD) comprise 1-2% of the population worldwide and over 4 million people living in the United States. IDD is a significant risk factor for premature morbidity or mortality due to preventable illness or deterioration and is associated with a 20-year decrease in life expectancy. This is likely due in part to preventable health conditions, which are modifiable with the intervention of direct care providers in areas including nutrition, promotion of an active lifestyle and effective identification of health or functional deterioration. Adults with IDD are also at increased risk for neglect or mistreatment. This disparity has been thoroughly documented across multiple countries and in a variety of care settings. Contributing factors include resource availability, lack of person-centered care, management culture and care worker training. Practical and economical interventions may address the known disparities and challenges facing the large community of adults with IDD. To promote person-centered care, improve record-keeping/documentation, and aide in protecting the health and safety of this vulnerable population, we propose incorporation of a video into the evaluation of adults with IDD living outside the home.